Hicksian Income and Contemporary Accounting - Petrova, V. (Економічний вісник Донбасу, 2015)
This article deals with the concept of income of one of the most influential economists of the 20th century - John Richard Hicks, which left deep trails in the theory of accounting. Hick’s ideas are both theoretically presented and practically illustrated. The way they have been transferred to modern accounting by IASB and FASB is analyzed. The criticisms of the use of the Hicksian income as a theoretical foundation of concepts of income, earnings and capital maintenance as adopted by the Conceptual Framework for Financial Reporting are also discussed in the article. Стаття присвячена поняттю доходу в теорії одного з найвпливовіших економістів ХХ століття - Джона Річарда Хикса, який залишив глибокий слід в теорії бухгалтерського обліку. Його ідеї представлені і проілюстровані як теоретично, так і практично. Проаналізовано як вони були трансформовані в сучасному бухгалтерському обліку в МСФЗ і РСФО. Критика використання теорії доходу Хикса як теоретичної основи поняття доходу, прибутку і капіталу представлені як концептуальні основи фінансової звітності і також обговорюються в статті. Это статья посвящена понятию дохода в теории одного из самых влиятельных экономистов ХХ века - Джона Ричарда Хикса, которая оставила глубокий след в теории бухгалтерского учета. Его идеи представлены и проиллюстрированы как теоретически, так и практически. Проанализировано как они были трансформированы в современном бухгалтерском учете в МСФО и ССФУ. Критика использования теории дохода Хикса как теоретической основы понятия дохода, прибыли и капитала представлены как концептуальные основы финансовой отчетности и также обсуждаются в статье.